Implementation of the Explicit Instruction Model for Mastery of Maharah Al-Kalam Arabic Language Learning for Class VII of SMP Al-Qur'an Zaenuddin Kramat Tegal - Mu'tafi, Ali; Ma’mun, Mohamad Subkhan; Faturrokhman, Faturrokhman (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
This thesis aims to find out the process of learning Arabic with the Explicit Instruction model in mastering Maharah Al-Kalam at SMP Al-Qur'an Zaenudin Kramat Tegal. To find out the supporting factors and inhibiting factors for the application of the Explicit Instruction model in learning Arabic at SMP Al-Qur'an Zaenudin Kramat, Tegal. To find out the evaluation technique for mastering Maharah Al-Kalam in learning Arabic using the Explicit Instruction model at SMP Al-Qur'an Zaenudin Kramat, Tegal. This thesis uses a qualitative approach, where the type of research is descriptive field. Data collection techniques use Observation, Interviews and Documentation. The analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study showed that Arabic language learning for class VII at SMP Al-Qur'an Kramat Tegal uses the Explicit Instruction model with teaching materials of the Asmaul Yaumiyah book and the Af'alul book which focus on mastering Maharah Al-Kalam. Systematic learning structure, explicit instruction-based approach, and gradual exercises help students understand language patterns more clearly. Lecture, question and answer, and group discussion methods enrich the learning process, making it more interactive. Periodic evaluations ensure students understand the material before moving on to the next material. Overall, the combination of teaching methods with this model has been proven to improve students' Arabic speaking skills significantly. Arabic language learning with the Explicit Instruction model at SMP Al-Qur'an Zaenudin is supported by the kitab Asmaul Yaumiyah and Af'alul, teacher competence, a conducive learning environment, and active student involvement. These factors help students master the Maharah Al-Kalam better. However, several obstacles are still faced, such as limited student vocabulary, limited learning time, and differences in student abilities in understanding the material given. Therefore, more varied teaching strategies and additional support are needed to optimize learning outcomes.